Brave new surfactant world revisited by thermoalkalophilic lipases: computational insights into the role of SDS as a substrate analog. Issue 3 (3rd January 2023) - Shehata, Mohamed; Ünlü, Aişe; Iglesias-Fernández, Javier; Osuna, Sílvia; Sezerman, O Ugur; Timucin, Emel
Abstract : SDS binds to the catalytic cleft of a thermostable lipase and partially opens its closed lid. Abstract : Non-ionic surfactants were shown to stabilize the active conformation of thermoalkalophilic lipases by mimicking the lipid substrate while the catalytic interactions formed by anionic surfactants have not been well characterized. In this study, we combined μs-scale molecular dynamics (MD) simulations and lipase activity assays to analyze the effect of ionic surfactant, sodium dodecyl sulfate (SDS), on the structure and activity of thermoalkalophilic lipases. Both the open and closed lipase conformations that differ in geometry were recruited to the MD analysis to provide a broader understanding of the molecular effect of SDS on the lipase structure. Simulations at 298 K showed the potential of SDS for maintaining the active lipase through binding to the sn -1 acyl-chain binding pocket in the open conformation or transforming the closed conformation to an open-like state. Consistent with MD findings, experimental analysis showed increased lipase activity upon SDS incubation at ambient temperature. Notably, the lipase cores stayed intact throughout 2 μs regardless of an increase in the simulation temperature or SDS concentration. However, the surface structures were unfolded in the presence of SDS and at elevated temperature for both conformations. Simulations of the dimeric lipase were also carried out and showed reduced flexibility of the surface structures which were unfolded in the monomer, indicating the insulating role of dimer interactions against SDS. Taken together, this study provides insights into the possible substrate mimicry by the ionic surfactant SDS for the thermoalkalophilic lipases without temperature elevation, underscoring SDS's potential for interfacial activation at ambient temperatures.